2018
DOI: 10.1136/bcr-2018-225072
|View full text |Cite
|
Sign up to set email alerts
|

Congenital colonic stenosis with absent caecum and appendix: a rare association

Abstract: Congenital colonic stenosis is a rare condition with less than 20 cases reported in the literature since 1966. We report an interesting case of a 7-month-old baby girl who presented with features suggestive of acute intestinal obstruction. On exploration, it was a case of ascending colon stenosis with absence of caecum and appendix. A double barrel ileocolostomy was performed. The histopathology confirmed the diagnosis of colonic stenosis and ruled out the presence of Hirschsprung’s disease in the distal colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 12 publications
0
5
2
Order By: Relevance
“…However, contrast enema was not conclusive in making a preoperative diagnosis of CCS in our study similar to other reported cases where the diagnosis of CCS could be made only during laparotomy. The length of stenotic colon may vary 1–16.5 cm;[ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 ] while in our study, it ranged 1–8 cm. CCS may involve any part of the colon, namely ascending colon,[ 2 3 5 10 11 14 ] transverse colon,[ 2 4 10 14 ] descending colon,[ 2 4 7 12 14 ] and sigmoid colon.…”
Section: Discussioncontrasting
confidence: 49%
See 4 more Smart Citations
“…However, contrast enema was not conclusive in making a preoperative diagnosis of CCS in our study similar to other reported cases where the diagnosis of CCS could be made only during laparotomy. The length of stenotic colon may vary 1–16.5 cm;[ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 ] while in our study, it ranged 1–8 cm. CCS may involve any part of the colon, namely ascending colon,[ 2 3 5 10 11 14 ] transverse colon,[ 2 4 10 14 ] descending colon,[ 2 4 7 12 14 ] and sigmoid colon.…”
Section: Discussioncontrasting
confidence: 49%
“…The length of stenotic colon may vary 1–16.5 cm;[ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 ] while in our study, it ranged 1–8 cm. CCS may involve any part of the colon, namely ascending colon,[ 2 3 5 10 11 14 ] transverse colon,[ 2 4 10 14 ] descending colon,[ 2 4 7 12 14 ] and sigmoid colon. [ 4 5 6 13 14 ] The most commonly involved colonic segments are descending and sigmoid colon.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations